Analisis Optimasi Multiple Travelling Salesman Problem Time Window Pada Algoritme Genetika Terhadap Pemilihan Rute Pengiriman Barang J&T Express Surabaya - Eko Wahyu Hidayat; Agus Wahyu Widodo; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
J&T Express is a company engaged in the service of shipping the goods. The process of delivery of the goods on the J&T Express speed levels very seriously, because it has to be timely in serving all the customers with the maximum time duration of 1x24 hours to 2x24 hours. Delivery of the goods on the field do not always meet the target because some non technical issues. One of the reasons is the level of congestion in some cities that make the delivery of goods is hampered. This research has the objective to create a system that is able to find a line with a low level of congestion and are able to find routes with the fastest travel time that you visit our sales more than one, that problem is called with Multiple Travelling Salesman Problem Time Window (MTSP-TW). Genetic algorithms is one method that can be used to solve the problem of MTSP-TW, so it can search through the route with a fastest journey time. The test results on the analysis of the selection of shipping routes shows that the crossover one cut point with mutation insertion produces a fitness better combination than other reproduction, and the results of the selection of the route of the system generates a time faster than the route choice company.